2022
DOI: 10.1007/s11274-022-03499-8
|View full text |Cite
|
Sign up to set email alerts
|

Influencing factors on ureolytic microbiologically induced calcium carbonate precipitation for biocementation

Abstract: Microbiologically induced calcium carbonate precipitation (MICP) is a technique that has received a lot of attention in the field of geotechnology in the last decade. It has the potential to provide a sustainable and ecological alternative to conventional consolidation of minerals, for example by the use of cement. From a variety of microbiological metabolic pathways that can induce calcium carbonate (CaCO3) precipitation, ureolysis has been established as the most commonly used method. To better understand th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…The measured electrical conductivities, as shown in Figure 2, were observed to be higher for the samples augmented with ammonium chloride, particularly for the lowest and highest calcium concentrations used. The inhibiting effect of a high calcium concentration on the MICP process has been reported [9,42]. The ammonium chloride addition appears to counteract against this inhibiting effect and otherwise stimulated the MICP process when the calcium concentration drops below 0.5 M. The R squared values in Figure 2 are indicative of a good fit between the polynomial trendlines on the Excel plot and the data.…”
Section: Batch Test Resultsmentioning
confidence: 52%
“…The measured electrical conductivities, as shown in Figure 2, were observed to be higher for the samples augmented with ammonium chloride, particularly for the lowest and highest calcium concentrations used. The inhibiting effect of a high calcium concentration on the MICP process has been reported [9,42]. The ammonium chloride addition appears to counteract against this inhibiting effect and otherwise stimulated the MICP process when the calcium concentration drops below 0.5 M. The R squared values in Figure 2 are indicative of a good fit between the polynomial trendlines on the Excel plot and the data.…”
Section: Batch Test Resultsmentioning
confidence: 52%
“…We found that bacteria at 30 °C had statistically significant precipitation compared to their counterparts, indicating that temperature plays a significant role in calcium carbonate precipitation (Table 5 ). Previous studies have also found temperatures between 25 and 35 °C ideal for calcium carbonate precipitation due to superior bacterial growth and metabolic activity (Rui and Qian 2022 ; Rollakanti and Srinivasu 2022 ; Erdmann and Strieth 2023 ). The observed trend of enhanced cementation in the top half of the sand column aligns with previous research findings, suggesting a common phenomenon attributed to bacterial growth dynamics and oxygen availability within the column (He et al 2020 ; Chu et al 2012 ; Fronczyk et al 2023 ).…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, previous SEM observations have revealed a close agglomeration of rhombohedral and blocky calcite structures when subjected to the influence of a calcium chloride/urea cementation solution. (Naveed et al 2020 ; Sun et al 2019 ; Erdmann and Strieth 2023 ). Thus, temperature also plays a role in determining the shape of the crystals and their application in soils (Bu et al 2022 ; Peng and Liu 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, any decrease in calcium in the intestinal lumen raises the amount of free absorbable oxalate ( Asplin, 2016 ). Struvite calculi are classified as infectious lithiasis ( Flannigan et al, 2014 ), because their presence implies the intervention of a ureolytic germ capable of raising urine alkalinity sufficiently to cause the simultaneous precipitation of ammonium and magnesium phosphates ( Arias et al, 2017 , Erdmann and Strieth, 2023 ). The treatment of these two types of stones relies on conventional techniques such as extracorporeal lithotripsy and percutaneous nephrolithotomy, as well as on costly drugs that can cause side effects ( Mohamed et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%